Examining the Effectiveness of Year-Round School Calendars on Improving Educational Attainment Outcomes Within the Context of Advancement of Health Equity: A Community Guide Systematic Review - Finnie, Ramona K. C. (J Public Health Manag Pract, 2019)
Students may lose knowledge and skills achieved in the school year during the summer break, with losses greatest for students from low-income families. Community Guide systematic review methods were used to summarize evaluations (published 1965–2015) of the effectiveness of year-round school calendars (YRSCs) on academic achievement, a determinant of long-term health. In single-track YRSCs, all students participate in the same school calendar; summer breaks are replaced by short “intersessions” distributed evenly throughout the year. In multi-track YRSCs, cohorts of students follow separate calendar tracks, with breaks at different times throughout the year. An earlier systematic review reported modest gains with single-track calendars and no gains with multi-track calendars. Three studies reported positive and negative effects for single-track programs and potential harm with multi-track programs when low-income students were assigned poorly resourced tracks. Lack of clarity about the role of intersessions as simple school breaks or as additional schooling opportunities in YRSCs leaves the evidence on single-track programs insufficient. Evidence on multi-track YRSCs is also insufficient.